Victim, perpetrator, or what else? : generational and gender perspectives on children, youth, and violence - Bühler-Niederberger, Doris; Alberth, Lars (Emerald Publishing Limited, 2019)
Children, while being the most victimised group in society, rarely become a topic of sociological research, neither as victims nor as perpetrators. The sociological discussion on power and violence happens beyond generation as an important dimension of social structure, and in many respects also beyond gender aspects that are inseparably linked to generational violence. This is a severe omission when the extent of violence in a society needs to be understood, as well as the structures and processes perpetuating violence or opposing its abolition. It is also a serious obstacle when understanding the position of children and exploring the social meaning of childhood. This volume addresses this blind spot in sociology. It does so by mapping the ways that children and young people are considered victims or perpetrators by their societies and consequently the ways that their societies react. The chapters analyse a variety of phenomena in different countries of the Global North and South. All of these phenomena may be considered to include acts of violence toward children and adolescents, or those committed by them. Thus, violence is addressed as one of the major building blocks of the scope and qualities of children's agency, limiting the social recognition of their rights as members of their respective societies. With a global reach and cutting-edge research, this book will prove an invaluable text for researchers and leaders in the fields of comparative childhood research and sociology of violence alike.
Includes index.
Keywords: Abused children -- Social aspects.; Abused children -- Social conditions.; Child abuse -- Social aspects.; Victims of family violence -- Social conditions.; Family violence -- Social aspects.; Juvenile delinquency.; Social Science -- Children's Studies.; Child abuse.; elektronické knihy; electronic books